Rekontruksi Pendidikan Budaya â€œRarangaken Sawahâ€ Bagi Anak-anak Kecamatan Cipatujah Kabupaten Tasikmalaya - Trisna Gumilar; Samson CMS; Kusnandar Kusnandar (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2016)
Abstract: Rangraken Sawag is one manifestation of an agrarian culture in District Cipatujah, Tasikmalaya, West Java. This culture in unique because it contains a high aesthetic, in addition to its usefulness in helping farmers maintain the fields. The existence of this culture are now showing symptoms of decline. People are starting to forget this thing., especially the younger generation. Therefore, in a series of conservation activities organized by the food culture Community Service team Padjadjaran University and assisted by Sunda Pakidulan Dangiang community, local government officials and community leaders, the recontruction has been initiated especially for children. The Purpose of this implementation to reintroduce, instill a love, and fostering cultural creativity based society. Keyword: Reconstruction, Education, Children.